Samoprocjena kompetencija učenika završnih razreda srednjih škola i odabrane grupe studenata za rad sa suvremenim audiovizualnim tehnologijama / Self-competency Competence Final Year Students of Secondary School and Selected Groups of Students for Work Suggested Audiovisual Technologies - Varga, Matija (Pregled: časopis za društvena pitanja / Periodical for social issues, 2020)
The paper on "self-assessment of competences of final grade students of secondary schools and selected groups of students for work with audiovisual technologies" brings research on the application of information and communication technologies and audiovisual technologies as well as research on self-assessment competences of final grade students of high schools and students working with audiovisual technologies. The basic hypothesis H1 is set out in this paper: The pupils of the final grades of secondary and first-year students have enough competences, knowledge and skills to work with modern audiovisual technologies. Also, sub-pilots H11 were set to determine the impact of time spent on a personal computer and smartphone for the needs of schools and faculties on acquiring competences for working with modern audiovisual technologies, which reads: H11: Time spent on a personal computer and a smartphone for educational purposes and the faculty affect the acquisition of competences of a group of respondents to work with modern audiovisual technologies and H12: it is possible to determine the respondents' opinion on formal education (school and college) in improving their achievements in the development of competences and skills of respondents, which reads: H12: Formal Education (school and college) helps to improve the achievements and to develop the competences and skills of respondents to work with modern audiovisual technologies. The respondents were 3rd and 4th grade students of secondary school and students of the first and second year of the faculty. In the questionnaire process, respondents conducted self-assessment competencies.